Pembentukan Brand Awareness UMKM Kripik Pisang Untuk Meningkan Penjualan melalui Media Sosial Di Desa Gondosuli dalam Perspektif Ekonomi Syariah - Usmiatul Hasanah; Mohammad Syaiful Su’ib (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to explore the strategies used by banana chip MSMEs in Gondosuli Village to strengthen brand awareness through social media while preserving local socio-cultural values. A descriptive qualitative approach with a case study design was employed. Data were collected through in-depth interviews with ten key informants consisting of MSME owners, consumers, and village officials, supported by participant observation on WhatsApp Business and TikTok, as well as documentation of digital content and product packaging. The findings reveal three main branding strategies: utilizing social media for local product storytelling, integrating cultural symbols and local language into digital content, and promoting community collaboration in disseminating brand messages. These strategies enhance consumers’ emotional attachment while preserving local cultural identity in the digital environment. From the perspective of Islamic economics, digital marketing should uphold the principles of honesty, trustworthiness, transparency, and fairness. The novelty of this study lies in integrating local cultural values into social media-based branding strategies, providing practical implications for strengthening MSME competitiveness, expanding market reach, and supporting community-based economic empowerment through culturally rooted digital marketing.